The influence of chronotype in the daily lives of young children. (15th March 2016) - Zimmermann, Laura K.
ABSTRACT: Research on chronotypic differences has been conducted for many years, however, until recently, little attention has been paid to young children. The current study examined the influence of morningness–eveningness in the daily lives of 2 to 4 year olds (291 females, 230 males, 8 gender not given) via an online survey completed by 529 mothers from across the United States. The results replicated previous findings on chronotypic differences in sleep-wake patterns and the development of morningness–eveningness in early childhood. The influence of chronotype on sleep habits, daily routines and schedules was also explored. At both bed and wake times, mothers of evening type (E-type) children were more likely to report challenges. For a while, morning type (M-type) children tended to fall asleep easily and wake themselves up in the morning, E-types were more likely to show bedtime resistance, wake in a negative mood and have conflicts with their parents. In the morning, mothers of M-type children often stuck to their normal routine on days when the child had to be somewhere at 7:00 am, whereas mothers of E-type children employed different strategies to get their child up and out the door. Bedtime routines and daily schedules also differed by chronotype. Individual differences in morningness–eveningness and their impact on sleep-wake patterns and social interactions are evident early on. A greater understanding of how they affect the lives of young children and their future development is needed.